Task-switching mechanisms under methamphetamine cravings: sex differences in cued and voluntary task-switching - Jiang, Huan; Yang, BinJie; Huang, HanZhi; Zhao, Dong; Li, HuiLing; Chen, ZhiYing; Jin, Shengyi; Zhou, Qiang (Frontiers in Neuroscience, 2024)
IntroductionThis study explored the effects of task-switching type and sex on the task-switching ability of methamphetamine abstainers, as well as the differences in brain mechanisms under drug cravings under drug cravings using near-infrared spectroscopy.MethodsCraving-inducing videos were used to arouse 20 methamphetamine abstainers (including 10 men), whose switching ability was then assessed using voluntary and cued task-switching exercises.ResultsDuring task-switching under methamphetamine cravings, the activation of the premotor cortex (PMC), supplementary motor area (SMA), frontal eye field (FEF), and dorsolateral prefrontal cortex (DLPFC) in women was significantly stronger than in men, while the activation of FEF in men was significantly stronger than in women. Voluntary task-switching induced stronger FEF activation than cued task-switching. During the latter, women exhibited stronger activation in the anterior prefrontal cortex (aPFC) than men.DiscussionBoth men and women showed brain lateralization during task-switching under methamphetamine cravings. Men tended to adopt proactive control and use a top-down dominant strategy to start a new task. Women, however, tend to use a bottom-up strategy focusing on inhibiting old tasks and emotional switching. Moreover, in cued task-switching, the result shows women paid more attention to emotional processing than did men, which suggests that different task-switching training programs should be developed according to sex.